Culture^2 Theorizing Theory for the Twenty-First Century, Vol. 1 - Kelleter, Frank; Starre, Alexander (Digitale Gesellschaft, 2022)
How to do cultural studies in the twenty-first century? This essay collection is not a handbook, encyclopedia, or a »state of the field« compendium. Instead, it is a reflexive exercise in cultural studies, featuring fifteen accessible essays on a selection of critical key works published since 2000. The contributors aim to provide readers with a fresh and engaging look at recent criticism, exploring the interdisciplinary traffic of theories, methods, and ideas within the field of cultural and literary studies. This book shows how the work of Lauren Berlant, Rita Felski, Fred Moten, Anna Tsing, and others can inspire new thinking and theorizing for the twenty-first century.